2012
DOI: 10.5755/j01.ee.23.2.1539
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Career and Competency: Verification of Theoretical Model Validity

Abstract: In a constantly changing environment, a new approach to an organization as a performance system where employee'ss are becoming the most important factor determining the efficiency of organizational performance is developing. However, the ability to attract and retain competent specialists is often a challenge for the organization since it has to recognize the range of factors that motivate each employee's and serve as incentives for activity. One of such incentives is the possibilities to make a successful car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…Based on a study done by Chreptaviciene & Starkute (2012), it is found that career development is influenced by the competencies possessed by a person in an organization. The level of competency should be developed along with the increase in one's career.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Based on a study done by Chreptaviciene & Starkute (2012), it is found that career development is influenced by the competencies possessed by a person in an organization. The level of competency should be developed along with the increase in one's career.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Chowdhury & Murzi (2020), Juodeikaitė & Fominienė (2016), Savanevičienė et al (2008), Lepaitė (2003) savo tyrimuose nustatė, kad globalėjančiose įmonėse sėkminga darbuotojo veikla priklauso nuo gebėjimo prisitaikyti prie sparčiai kintančios aplinkos, todėl būtina orientuotis į šiandienos keliamus reikalavimus specialistų kompetencijoms ir numatyti, kokių kompetencijų reikės ateityje. Chreptaviciene & Starkute (2012) nustatė, kad specialisto imlumas naujoms profesinėms žinioms, gebėjimas analizuoti ir priimti sprendimus, vadybos gebėjimai ir bendravimo įgūdžiai yra svarbūs siekiant karjeros aukštumų. Pasak Rutkausko ( 2006), svarbu, kad darbuotojai gebėtų priimti techninius sprendimus, atitinkančius gamyklos vadovų iškeltus vykdomos veiklos tikslus.…”
Section: Lentelė Logistikos Specialistų Kompetencijų Charakteristikosunclassified
“…Logistikos specialistų inžinerinės kompetencijos sąvoka apibrėžiama remiantis įvairių mokslo krypčių mokslininkų požiūriu į inžinerinę kompetenciją ir šios sąvokos traktuotę. Chreptaviciene & Starkute (2012) tyrimuose akcentavo, kad personalo įtraukimo į sprendimų priėmimo procesą techniniais klausimais inžinerinė kompetencija padėtų išspręsti nemažai problemų. Iškylančios problemos yra susijusios su sprendimų priėmimu ir įgyvendinimu.…”
Section: Logistikos Specialistų Inžinerinės Kompetencijosunclassified